P73 Preliminary results of the Study of Acute Liver Transplant (SALT): NSAID exposure and risk of acute liver failure leading to transplantation in 7 European countries. (6th September 2011) - Thorburn, D; Gulmez, E; Lignot, S; Larrey, D; de Vries, C; Perez-Gutthann, S; Montastruc, J L; Sturkenboom, M; Benichou, J; Velo, G; Caputi, A; Salvo, F; et al.
Abstract : Introduction: The risk of acute liver failure (ALF) related to NSAIDs is still discussed and the European Medicines Agency requested a study investigating this. University Bordeaux Segalen conducted the study independently. Aim: To estimate the incidence rates of ALF leading to registration for liver transplantation (LT) in patients exposed to NSAIDs. Method: Multinational, multicentre, case-population study performed in France, Greece, Ireland, Italy, the Netherlands, Portugal, and the UK retrospectively evaluating a 3-year period (2005–2007) in adults. Data of ALF cases were sought through liver transplant registries and hospital records. Demographic and clinical data were collected for all ALF cases and drug use information was collected for the exposure window of 30 days prior to index date (ID, initial symptoms of liver disease). For ALF cases exposed to NSAIDs (ATC code M01A), rate per million treatment-years (tt-yrs) was calculated using sales data from IMS. Poisson CIs (95% CI) were estimated. Results: In the seven participating countries, 62 LT centres were identified and contacted, five were excluded (four paediatric, one oncology), and 50 actively contributed data before database lock. Among the 8824 patients identified from LT lists for the period 2005–2007, 500 were cases of ALF: 197 with identified clinical cause, 21 with incomplete or unavailable medical files, and 241 drug-exposed without identified clinical cause. Among the latter, 34 were exposed to at least one NSAID, 123 exposed to other drugs, and 84 were acute drug intoxications. Mean age of NSAID-exposed ALF cases was 43.8 years, 24 were female. Event rates per million treatment-years were 4.4 (95% CI 3.0 to 6.1) for all NSAIDs pooled, 5.6 (2.4 to 11.1) for nimesulide (8 cases), 5.8 (2.8 to 10.6) for ibuprofen (10 cases), 4.5 (1.5 to 10.4) for diclofenac (5 cases), and 4.7 (1.0 to 13.6) for ketoprofen (3 cases). 71 of the 157 non-intoxication cases had been exposed to paracetamol (9.8 per million treatment-years, 95% CI 7.7 to 12.4), and 83 of the 84 intoxications. Conclusion: In seven countries over 3 years only 34 NSAID-exposed ALF cases leading to registration for LT were identified with no differences in incidence rates per million tt-yrs among the most used NSAIDs. Non-overdose paracetamol-associated liver failure was twice more common.